PSCA and Oct-4 Expression in the Benign and Malignant Lesions of Gallbladder: Implication for Carcinogenesis, Progression, and Prognosis of Gallbladder Adenocarcinoma. (1st August 2013) - Zou, Qiong; Yang, Leping; Yang, Zhulin; Huang, Jiangsheng; Fu, Xi
Abstract : PSCA and Oct-4 have been thought as markers of cancer stem cells. Although overexpression of PSCA and Oct-4 in cancer has been reported, little is known about the clinical and pathological significance with PSCA and Oct-4 expression in gallbladder adenocarcinoma. In this study, overexpression of PSCA and Oct-4 was detected in gallbladder adenocarcinoma (54.6% and 55.6%). Less expression of PSCA and Oct-4 was detected in the pericancerous tissues (19.6% and 21.7%), gallbladder polyps (13.3% and 13.3%), and gallbladder epithelium with chronic cholecystitis (14.3% and 14.3%). The overexpression of PSCA and Oct-4 was significantly associated with differentiation, tumor mass, lymph node metastasis, invasion of gallbladder adenocarcinoma, and decreased overall survival. Our study suggested that overexpression of PSCA and Oct-4 might be closely related to the carcinogenesis, progression, metastasis, or invasive potential and prognosis of gallbladder carcinoma.